Obrození tanga: nostalgie, naslouchání, experiment - Gotlib, Matvei (Lidé města, 2023)
This article examines the history and culture of Argentinian tango as a translocal social dance and emphasizes its revivalist component along with other characteristic features: nostalgia, listening, and experimentation. It represents the partial and the preliminary result of the author’s anthropological research that they are currently conducting as part of the doctoral programme at the Faculty of Humanities of Charles University in Prague. The author concludes that both nostalgic beliefs and the desire to create something new contribute to the process of tango revival.